Effectiveness evaluation of pit and fissure sealing for first permanent molars in children in Haizhu District, Guangzhou after 3 years - CHEN Chunyan, TAN Fengqing, YANG Yan, LIU Xia (口腔疾病防治)
Objective To investigate the effect of a free pit and fissure sealing program for caries prevention on first permanent molars (six-year molars) in Haizhu District, Guangzhou, three years after its implementation in 2019. The study aims to provide a reference for the future development of pit and fissure sealing programs for children’s first permanent molars and the effective prevention and treatment of permanent tooth caries in children. Methods A random sampling method was used. In 2022 October, 270 sixth-grade primary-school students in Haizhu District, Guangzhou, who had participated in the free pit and fissure sealing program for their first permanent molars in 2019, were placed in the sealant group. Another 223 age-matched students from the same schools who met the criteria for the pit and fissure sealing but did not participate in the program were placed in the control group. The first permanent molars of students in both groups were examined. The retention status of the sealant and the caries status of the first permanent molars were recorded for the sealant group, and the caries status of the first permanent molars was recorded for the control group. The 2022 results were compared with the results of a prior pit and fissure sealing program implemented in Haizhu District in 2011, three years after its implementation. Results Compared with the control group, the caries rate in the sealant group decreased (15.56% vs. 21.52%, P>0.05), the caries detection rate was significantly lower (6.12% vs. 9.00%, P<0.001), and the mean number of decayed teeth was significantly reduced (0.19 vs. 0.37, P<0.001). Compared with the results of the pit and fissure sealing program in Haizhu District in 2011 (in 2014, the retention rate of the first permanent molar sealant was 65.56%, the intact rate was 42.25%, and the protection rate was 38.34%), the results of the pit and fissure sealing program in Haizhu District in 2019 [in 2022, the retention rate of the first permanent molar sealant was 86.09% (P<0.001), the intact rate was 47.00% (P<0.001), and the protection rate was 51.97%] were improved. Conclusion The quality of the pit and fissure sealing program for the first permanent molars in Haizhu District, Guangzhou in 2019 was good. It reduced the caries detection rate, and the retention rate of the sealant was maintained at a high level. However, the intact rate was less than 50%; therefore, it is necessary to vigorously promote oral-health education and examinations in all age groups, and to be attentive to the re-examination and re-sealing of fissure sealants.